2020
DOI: 10.48550/arxiv.2002.06162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Breakthrough Listen Search for Intelligent Life: A 3.95-8.00 GHz Search for Radio Technosignatures in the Restricted Earth Transit Zone

Sofia Z. Sheikh,
Andrew Siemion,
J. Emilio Enriquez
et al.

Abstract: We report on a search for artificial narrowband signals of 20 stars within the restricted Earth Transit Zone as a part of the ten-year Breakthrough Listen (BL) search for extraterrestrial intelligence. The restricted Earth Transit Zone is the region of the sky from which an observer would see the Earth transit the Sun with an impact parameter of less than 0.5. This region of the sky is geometrically unique, providing a potential way for an extraterrestrial intelligence to discover the Solar System. The targets… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To search for narrowband signals, we used the turboSETI code (Enriquez et al 2017) over a Doppler drift rate range of ±4 Hz s −1 and a signal-to-noise (S/N) threshold of 10 with the ∼2.79 Hz / ∼18.25 s data product, broadly following the steps described by Price et al (2020) and Sheikh et al (2020). Any continuous narrowband signals associated with pointings toward Kepler-160 would appear in all 3 of the ON observations and in none of the OFF observations.…”
Section: Resultsmentioning
confidence: 99%
“…To search for narrowband signals, we used the turboSETI code (Enriquez et al 2017) over a Doppler drift rate range of ±4 Hz s −1 and a signal-to-noise (S/N) threshold of 10 with the ∼2.79 Hz / ∼18.25 s data product, broadly following the steps described by Price et al (2020) and Sheikh et al (2020). Any continuous narrowband signals associated with pointings toward Kepler-160 would appear in all 3 of the ON observations and in none of the OFF observations.…”
Section: Resultsmentioning
confidence: 99%
“…Our best upper limit, from Table 3 of 6.2 × 10 12 W (not for a known exoplanet) approaches a 50% improvement on our best upper limit from Tingay et al (2018), still noting that an EIRP of 10 12 W is high compared to the highest power transmitters on Earth at these frequencies (see Tingay et al (2016) for a discussion). Sheikh et al (2020) recently completed an in-depth analysis of 20 stars within the Earth transit zone between 3.95-8 GHz with the NRAO Green Bank Telescope (GBT). They determined an EIRP of detectable narrow-band signals that ranged from 47-17590×10 9 W for stellar distances between 7-143 pc.…”
Section: Discussionmentioning
confidence: 99%
“…These are similar distances to the stars we present in Table 3 for the nearby stars from Gaia in the Vela field, but our sample represents a much larger population of on-average closer sources. Sheikh et al (2020) also convert their EIRP values to the fraction of signal capacity for the Aricebo Transmitter (L A ). Their value of 0.033 for a star at 27 pc is a factor of two lower than for a star in our survey at the same distance (0.068), recognising the difference in frequency between the GBT and the MWA and the fact that the GBT has better frequency resolution than the MWA.…”
Section: Discussionmentioning
confidence: 99%
“…The Earth transits the Sun as seen by observers at stars in this direction. It has been suggested that ETIs that observe Earth transits would be especially motivated to broadcast in our direction because they know a habitable planet exists; furthermore, the transit itself can be used for synchronization (Shostak 2004;Heller & Pudritz 2016;Sheikh et al 2020). Note-Solar?…”
Section: A113 Not Realmentioning
confidence: 99%
“…Despite searches spanning several decades, no compelling evidence for ETIs has been found by the SETI community to date (e.g., Horowitz & Sagan 1993;Griffith et al 2015;Pinchuk et al 2019;Lipman et al 2019;Price et al 2020;Sheikh et al 2020). The continuing lack of a discovery among SETI efforts looking for various technosignatures is sometimes called the Great Si-1 A planet between Mars and Jupiter was "predicted" by the Titius-Bode Law.…”
Section: Introductionmentioning
confidence: 99%